Design of CSD based bi-orthogonal wavelet filter bank for medical image retrieval - Samantaray, Aswini Kumar; Gorre, Pradeep; Sahoo, Prabodh Kumar (e-Prime, 2023)
•In this work, design of a low-complex bi-orthogonal wavelet filter bank is proposed based on canonical signed digit (CSD) implementation.•The CSD technique has been applied to the filter bank to eliminate the power consuming multipliers and to reduce the number of shifters and adders in the implementation of bi-orthogonal FB.•In addition, the proposed bi-orthogonal wavelet FB is implemented on hardware using Field Programmable Gate Array (FPGA) board Kintex-7 from Xilinx.•The performance of the proposed method is tested on medical image retrieval application. Two-channel wavelet filter-banks (FBs) are universally used in many applications of signal processing. In this work, design of a bi-orthogonal wavelet FB with low complexity is suggested. The proposed design is based on canonical signed digit (CSD) implementation of the bi-orthogonal wavelet FB. CSD technique has been applied to the FB to eliminate the power consuming multipliers and to reduce the number of shifters and adders in the implementation of bi-orthogonal FB. The suggested FB design is suitable for the application of high speed signal processing applications. In addition, the proposed bi-orthogonal wavelet FB is implemented on hardware using Field Programmable Gate Array (FPGA) board Kintex-7 from Xilinx. It is found that the suggested bi-orthogonal wavelet FB attained low digital hardware requirement as compared to well-known rationalized existing bi-orthogonal wavelet FBs. The efficacy of the suggested wavelet FB is demonstrated on medical image retrieval application. NEMA, OASIS, and EXACT09, three publicly accessible medical image datasets, are utilized to measure the efficacy of image retrieval. It is shown that the suggested bi-orthogonal wavelet FB performs better than the bi-orthogonal wavelet FBs existing that are being used.